A single crystal cobalt-free positive electrode material, preparation method thereof and lithium ion battery
The single-crystal cobalt-free cathode material is directly synthesized through acid treatment and sintering, which solves the problems of cumbersome preparation process and low single-particle strength in the prior art, and realizes a high-performance single-crystal cathode material, improving the magnification and cycling performance.
Patent Information
- Application Number
- CN202210772876.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-30
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2042-06-30
AI Technical Summary
In the prior art, the process of preparing single-crystal cobalt-free cathode materials is cumbersome, and the obtained single particles are relatively low in strength, and metal segregation is prone to occur during the precipitation reaction, affecting electrochemical properties.
The polycrystalline cobalt-free cathode material is acid-treated and mixed with lithium salt to sinter it directly through grain boundary separation to synthesize the single-crystalline cathode material to avoid metal segregation and retain the electrochemical properties of the original cathode material.
Through this method, a single crystal cobalt-free cathode material with particle dispersion was obtained, which improved the rate performance and cycle performance, simplified the preparation process, avoided metal segregation, and met the needs of high-performance batteries.
Smart Images

Figure BDA0003724861660000141
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries and cobalt-free positive electrode materials, and relates to a single crystal cobalt-free positive electrode material, a preparation method thereof and a lithium ion battery. Background Art
[0002] In recent years, the development of the power battery market has entered the fast lane. As the most reasonable energy storage medium at present, the demand for lithium-ion secondary batteries has exploded. With the continuous improvement of production capacity, the demand for positive electrode materials has continued to increase. The three metals headed by nickel, cobalt and manganese, as the most mainstream elements of positive electrode materials, have rapidly increased in price, especially cobalt, whose price has nearly doubled from January 2018 to January 2022. As a result, battery prices are also rising. Therefore, the development of cobalt-free positive electrode materials shows strong application prospects.
[0003] It is worth noting that the discharge capacity of lithium nickel manganese oxide (NM) and lithium nickel cobalt manganese oxide (NCM) cathodes with the same Ni content at 0.1C is comparable. At the same time, the NM cathode exhibits better cycle stability and thermal stability than the NCM cathode. Therefore, the development of the NM cathode is expected to replace the NCM cathode. It is well known that single crystals have better safety and cycle performance than polycrystalline cathodes. At the same time, polycrystalline cathode materials have "grain seeds" with good crystal structure, so the use of polycrystalline to single crystal cathode materials has good development prospects.
[0004] CN112391671A discloses a method for reconstructing ternary single crystal materials from waste ternary polycrystalline materials, which comprises: mixing waste ternary polycrystalline materials with organic mixed solvents to form slurry, removing part of the solvent after ultrasonic treatment, and obtaining waste ternary polycrystalline material slurry; placing the waste ternary polycrystalline material slurry in a drum mixer for mixing, atomizing and spraying lithium manganate seed slurry into the drum mixer, and obtaining a material to be repaired; and performing multi-stage roasting of the material to be repaired in an air atmosphere to obtain a ternary single crystal material. The reconstruction method has simple process, short flow, and high economic added value, and can achieve high-value conversion of waste ternary materials, and the obtained single crystal material has good electrical properties.
[0005] CN114196829A discloses a method for recovering nickel-cobalt-manganese positive electrode materials of retired lithium-ion batteries, the method comprising: (1) crushing the nickel-cobalt-manganese positive electrode materials in retired lithium-ion batteries to obtain seed crystals, wherein the particle size D50 of the seed crystals is less than 500nm; (2) uniformly mixing the seed crystals with a mixed solution containing a nickel source, a cobalt source and a manganese source, adding a precipitant and a complexing agent for coprecipitation reaction to obtain a single crystal nickel-cobalt-manganese material precursor; (3) uniformly mixing the single crystal nickel-cobalt-manganese material precursor with a lithium source and calcining the mixture to obtain a single crystal positive electrode material. The method can convert the nickel-cobalt-manganese polycrystalline material in retired lithium-ion batteries into a nickel-cobalt-manganese single crystal material with excellent electrochemical performance, which can better meet the needs of high-performance battery development.
[0006] However, the preparation process of the above invention is complicated, the obtained single-particle single-crystal particles have low strength, and the process of generating precursors by precipitation reaction is prone to cause metal segregation, which affects the electrochemical performance. Summary of the invention
[0007] In view of the above problems existing in the prior art, the object of the present invention is to provide a single crystal cobalt-free positive electrode material, a preparation method thereof and a lithium ion battery. The present invention adopts direct grain boundary separation to synthesize single crystal positive electrode materials, which can retain the properties of the original positive electrode material (such as nickel-manganese gradient concentration), does not exist in the metal segregation process, and retains the electrochemical properties of the original positive electrode. The single crystal cobalt-free positive electrode material is prepared by the method of the present invention, which can improve the rate performance and cycle performance of the single crystal positive electrode material.
[0008] To achieve the above object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing a single crystal cobalt-free positive electrode material, the method comprising the following steps:
[0010] Acid treatment of polycrystalline cobalt-free cathode material is performed using an acid solution;
[0011] The acid-treated cobalt-free positive electrode material is mixed with a lithium salt and sintered to obtain a single crystal cobalt-free positive electrode material.
[0012] The method of the invention utilizes acid etching of polycrystalline cobalt-free positive electrode materials, and performs lithium addition and sintering to obtain single-crystal cobalt-free positive electrode materials, thereby obtaining positive electrode materials with primary particle dispersion and improving rate performance and cycle performance.
[0013] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0014] Preferably, the acid in the acid solution includes at least one of organic acid, sulfuric acid, hydrochloric acid and nitric acid, preferably organic acid. Compared with sulfuric acid, hydrochloric acid and nitric acid, organic acid containing three elements of C, H and O is used for etching. Impurity elements such as S, Cl and N will not be introduced due to decomposition, and there is no effect on the later positive electrode electrical performance. Therefore, organic acid is preferably used for etching.
[0015] Preferably, the organic acid comprises at least one of formic acid, acetic acid, propionic acid, butyric acid, caprylic acid, adipic acid, oxalic acid, malonic acid, succinic acid, maleic acid, tartaric acid, benzoic acid, phenylacetic acid, phthalic acid, terephthalic acid, valeric acid, caproic acid, capric acid, stearic acid and palmitic acid.
[0016] Preferably, the concentration of the acid solution is 1 mol / L to 2 mol / L, for example, 1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.5 mol / L, 1.7 mol / L, 1.8 mol / L or 2 mol / L.
[0017] Preferably, the acid treatment process is: adding the polycrystalline cobalt-free positive electrode material into an acid solution and stirring.
[0018] Preferably, during the acid treatment, the amount of polycrystalline cobalt-free cathode material added is 0.02 g / mL to 0.1 g / mL, such as 0.02 g / mL, 0.03 g / mL, 0.05 g / mL, 0.07 g / mL, 0.08 g / mL or 0.1 g / mL, etc. Among them, 0.02 g / mL is used as an example to illustrate its meaning, which means that the amount of polycrystalline cobalt-free cathode material added is 0.02 g per 1 mL of acid solution.
[0019] Preferably, during the acid treatment, the stirring temperature is 25°C to 60°C, for example, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C or 60°C; the stirring time is 8 to 20h, for example, 8h, 9h, 10h, 12h, 13h, 14h, 15h, 16h, 18h or 20h.
[0020] Preferably, the acid treatment is followed by separation, washing and drying. Optionally, the drying is followed by screening.
[0021] The present invention does not specifically limit the separation method, including but not limited to filtration and centrifugation.
[0022] In an optional embodiment, washing comprises: washing the separated powder with deionized water for more than three times, and then washing with ethanol for three times.
[0023] The present invention does not limit the drying method, which can be natural air drying or oven drying. For example, the washed sample can be placed in an oven and dried at 80° C. for 12 hours.
[0024] As a preferred technical solution of the method of the present invention, the particle size D50 of the cobalt-free positive electrode material after acid treatment is 0.8μm to 1.5μm, for example, 0.8μm, 1μm, 1.2μm, 1.3μm, 1.4μm or 1.5μm, etc.; the breaking strength is 30MPa to 45MPa, for example, 30MPa, 32MPa, 35MPa, 38MPa, 40MPa, 42MPa, 43MPa or 45MPa, etc.; the first power of the particle size D50 of the cobalt-free positive electrode material after acid treatment is denoted as a, and the cobalt-free positive electrode material after acid treatment is denoted as a. The breaking strength of the pole material is denoted as b, and a×b is 25MPa*μm to 60MPa*μm, for example, 25MPa*μm, 28MPa*μm, 30MPa*μm, 32MPa*μm, 34MPa*μm, 36MPa*μm, 38MPa*μm, 40MPa*μm, 42.5MPa*μm, 45MPa*μm, 47MPa*μm, 48MPa*μm, 50MPa*μm, 52MPa*μm, 55MPa*μm, 57MPa*μm or 60MPa*μm, etc.
[0025] Preferably, the indentation hardness of the cobalt-free positive electrode material after acid treatment is 4 GPa to 15 GPa, for example, 4 GPa, 6 GPa, 8 GPa, 10 GPa, 12 GPa, 13 GPa or 15 GPa, etc.; the Young's modulus is 60 GPa to 150 GPa, for example, 60 GPa, 65 GPa, 70 GPa, 75 GPa, 80 GPa, 85 GPa, 90 GPa, 95 GPa, 100 GPa, 105 GPa, 110 GPa, 115 GPa, 120 GPa, 130 GPa, 135 GPa, 140 GPa or 150 GPa, etc.; the ratio of Young's modulus to indentation hardness is 10 to 15, for example, 10, 11, 12, 13, 14 or 15, etc.
[0026] If the particle size D50 of the cobalt-free positive electrode material after acid treatment is too small, it may cause the subsequent sintering process to remain polycrystalline, and it is impossible to obtain a high-performance cobalt-free single crystal positive electrode material.
[0027] By designing the indentation hardness, Young's modulus and fracture strength of the cobalt-free positive electrode material after acid treatment, that is, rationally designing the above parameters of the primary cobalt-free particles, the mechanical properties of the cobalt-free single crystal positive electrode material can be effectively improved, which is helpful for the development of batteries with high compaction and high volumetric energy density.
[0028] Preferably, in the XRD spectrum of the cobalt-free positive electrode material after the acid treatment, the ratio of the (003) characteristic diffraction peak intensity to the (101) characteristic diffraction peak intensity is 2.0 to 2.5, such as 2.0, 2.1, 2.2, 2.3, 2.4 or 2.5, etc.; the ratio of the (003) characteristic diffraction peak intensity to the (104) characteristic diffraction peak intensity is 1.5 to 1.8, such as 1.5, 1.6, 1.7 or 1.8, etc. By designing the above-mentioned reasonable crystal structure orientation, it is helpful to improve the cycle stability and reduce the Li / Ni mixing.
[0029] As another preferred technical solution of the method of the present invention, the amount of the lithium salt added accounts for 5% to 10% of the mass of the cobalt-free positive electrode material after acid treatment, for example, 5%, 5.5%, 6%, 6.5%, 7%, 8%, 9% or 10%, etc.
[0030] Preferably, the sintering temperature is 900°C to 1100°C, for example, 950°C, 955°C, 960°C, 965°C, 970°C, 975°C, 980°C, 985°C, 990°C, 995°C, 1000°C or 1005°C.
[0031] Preferably, the sintering time is 8 h to 20 h, for example, 8 h, 9 h, 10 h, 12 h, 13 h, 14 h, 15 h, 16 h, 18 h or 20 h.
[0032] As a preferred technical solution of the method described in the present invention, the raw materials used for mixing the cobalt-free positive electrode material after the acid treatment also include a coating agent, and the coating agent includes at least one of ZrO2, Al2O3, Ta2O5, MoO3, SiO2, Y2O5, MgO, TiO2, WO3, Nb2O5, SrCO3 and La2O5.
[0033] Preferably, based on the mass of the single crystal cobalt-free positive electrode material, the amount of the coating agent used is 1000ppm to 3000ppm, for example, 1000ppm, 1200ppm, 1300ppm, 1500ppm, 1700ppm, 1800ppm, 2000ppm, 2200ppm, 2300ppm, 2500ppm, 2750ppm, 2800ppm or 3000ppm.
[0034] The present invention does not limit the source of the polycrystalline cobalt-free positive electrode material. For example, it can be recovered from waste lithium batteries, or prepared from raw materials.
[0035] The method of the present invention can be used as a recycling strategy for polycrystalline positive electrode materials. Compared with traditional recycling methods, the method of the present invention directly converts polycrystalline positive electrode materials into single-crystal positive electrode materials. The process is simple, the synthesized positive electrode material has excellent performance, and the excellent rate performance is helpful for the development of fast-charging batteries.
[0036] Preferably, the method for preparing the polycrystalline cobalt-free positive electrode material comprises the following steps: mixing a lithium salt, a cobalt-free precursor and an optional dopant, and reacting them at high temperature. The mixing method is not specifically limited, for example, a hand-held blender can be used for uniform mixing.
[0037] Preferably, in the method for preparing the polycrystalline cobalt-free positive electrode material, the cobalt-free precursor is Ni 0.65+a Mn 0.45-a (OH)2, wherein 0.00≤a≤0.25, for example, 0, 0.01, 0.02, 0.03, 0.05, 0.07, 0.08, 0.1, 0.12, 0.13, 0.15, 0.17, 0.18, 0.20, 0.22, 0.23 or 0.25, etc.
[0038] Preferably, in the preparation method of the polycrystalline cobalt-free positive electrode material, the particle size D50 of the cobalt-free precursor is 2.5 to 3.5 μm, such as 2.5 μm, 2.7 μm, 2.8 μm, 2.9 μm, 3.0 μm, 3.1 μm, 3.2 μm, 3.3 μm, 3.4 μm or 3.5 μm, etc.; the fracture strength is 10 to 15 MPa, such as 10 MPa, 11 MPa, 12 MPa, 13 MPa, 14 MPa or 15 MPa, etc.; the first power of the particle size D50 of the cobalt-free precursor is c, the fracture strength of the cobalt-free precursor is d, and c×d is 14 to 30 MPa*μm. Through the above definition, the strength of the particles can be guaranteed.
[0039] Preferably, in the preparation method of the polycrystalline cobalt-free positive electrode material, the indentation hardness of the cobalt-free precursor is 2GPa~3GPa, for example, 2GPa, 2.2GPa, 2.3GPa, 2.4GPa, 2.5GPa, 2.6GPa, 2.8GPa or 3GPa, etc.; the Young's modulus is 30GPa~60GPa, for example, 30GPa, 32GPa, 34GPa, 35GPa, 38GPa, 40GPa, 42.5GPa, 45GPa, 47GPa, 50GPa, 53GPa, 55GPa, 58GPa or 60GPa, etc.; the ratio of Young's modulus to indentation hardness is 15~30, for example, 15, 16, 18, 20, 23, 25, 27, 28 or 30, etc.
[0040] By designing the indentation hardness, Young's modulus and fracture strength of the cobalt-free precursor, the mechanical properties of the cobalt-free single crystal positive electrode material can be effectively improved, which is helpful for the development of batteries with high compaction and high volumetric energy density.
[0041] Preferably, in the method for preparing the polycrystalline cobalt-free positive electrode material, the dopant includes at least one of ZrO2, Al2O3, Ta2O5, MoO3, SiO2, Y2O5, MgO, TiO2, WO3, Nb2O5 and SrCO3.
[0042] Preferably, based on the mass of the single crystal cobalt-free positive electrode material, the amount of the dopant used is 500ppm to 5000ppm, for example, 500ppm, 800ppm, 1000ppm, 1100ppm, 1200ppm, 1500ppm, 1750ppm, 2000ppm, 2200ppm, 2400ppm, 2500ppm, 2600ppm, 2800ppm, 3000ppm, 3300ppm, 3500ppm, 3600ppm, 3800ppm, 4000ppm, 4500ppm or 5000ppm, etc.
[0043] Preferably, in the preparation method of the polycrystalline cobalt-free positive electrode material, the temperature of the high-temperature reaction is 700℃~900℃, for example, 700℃, 720℃, 730℃, 740℃, 750℃, 770℃, 780℃, 800℃, 825℃, 850℃, 880℃ or 900℃, etc.; the time of the high-temperature reaction is 8h~12h, for example, 8h, 9h, 10h or 12h, etc.
[0044] Preferably, in the preparation method of the polycrystalline cobalt-free positive electrode material, the heating rate of the high-temperature reaction is 2°C / min to 6°C / min, for example, 2°C / min, 3°C / min, 4°C / min, 5°C / min or 6°C / min; the cooling rate is 4°C / min to 6°C / min, for example, 4°C / min, 5°C / min or 6°C / min; the ratio of the cooling rate to the heating rate is 2 to 3, for example, 2, 2.2, 2.4, 2.5, 2.6, 2.8 or 3, etc.
[0045] In an optional embodiment, ultracentrifugal grinding and sieving steps are performed after cooling.
[0046] As a further preferred technical solution of the method of the present invention, the method comprises the following steps:
[0047] The first step: preparing a cobalt-free positive electrode material, after the lithium salt, the cobalt-free precursor and the dopant are uniformly mixed with a handheld mixer, the particle size D50 of the cobalt-free precursor is 2.5-3.5 μm, the fracture strength F is 10-15 MPa, the product of the fracture strength and the second power of the particle size D50 of the cobalt-free precursor is 14-30 MPa*μm, the indentation hardness (H) of the cobalt-free precursor is 2 GPa-3 GPa, the Young's modulus (E) is 30 GPa-60 GPa, and the ratio of the Young's modulus to the indentation hardness (W) is 15-30, reacting at a high temperature of 700°C-900°C for 8h-12h, cooling down, ultracentrifugal grinding and sieving;
[0048] Step 2: Add the prepared cobalt-free cathode material to 1mol / L-2mol / L oxalic acid solution, stir at 25℃-60℃ for 8h-20h, collect the powder after filtration, wash it with deionized water for more than three times, then wash it with ethanol for three times, put it into an oven to dry, sieve the dried cathode material to obtain cobalt-free cathode powder, the particle size D50 of the prepared cobalt-free cathode material is 0.8μm-1.5μm, the fracture strength F is 30MPa-45MPa, and the fracture strength is similar to that of the cobalt-free cathode material. The product of the first half of the particle size D50 is 25MPa*μm to 60MPa*μm, the indentation hardness (H) is 4GPa to 15GPa, the Young's modulus (E) is 60GPa to 150GPa, the ratio of Young's modulus to indentation hardness (W) is 10 to 15, the ratio of the intensity of the characteristic diffraction peak (003) to the intensity of the characteristic diffraction peak (101) in XRD is 2.0 to 2.5, and the ratio of the intensity of the characteristic diffraction peak (003) to the intensity of the characteristic diffraction peak (104) is 1.5 to 1.8;
[0049] In the third step, the cobalt-free positive electrode material powder obtained in the second step is uniformly mixed with the lithium salt and the coating agent, and then sieved and sintered to obtain the cobalt-free positive electrode material after being kept warm for 8h to 20h at 900°C to 1100°C, and the particle size D50 of the cobalt-free positive electrode material is 2.5μm to 3.5μm, the fracture strength F is 80MPa to 100MPa, and the product of the fracture strength and the square root of the particle size D50 of the cobalt-free positive electrode material is 100 to 100MPa. 200MPa*μm, indentation hardness (H) is 8GPa~15GPa, Young's modulus (E) is 150GPa~180GPa, the ratio of Young's modulus to indentation hardness (W) is 10~23, the ratio of the intensity of the characteristic diffraction peak (003) to the intensity of the characteristic diffraction peak (101) in XRD is 2.0~2.5, and the ratio of the intensity of the characteristic diffraction peak (003) to the intensity of the characteristic diffraction peak (104) is 1.5~1.8.
[0050] The present invention does not specifically limit the type of lithium salt, including but not limited to at least one of Li2CO3, LiOH and lithium nitrate.
[0051] In a second aspect, the present invention provides a single crystal cobalt-free positive electrode material prepared by the method described in the first aspect.
[0052] Preferably, the metal oxide coverage on the surface of the single crystal cobalt-free positive electrode material is 60% to 80%, for example, 60%, 62%, 65%, 67%, 68%, 70%, 72%, 73%, 75%, 77%, 78% or 80%, etc.
[0053] Preferably, the particle size D50 of the single crystal cobalt-free positive electrode material is 2.5μm to 3.5μm, for example, 2.5μm, 2.7μm, 2.8μm, 3.0μm, 3.2μm, 3.4μm or 3.5μm, etc.; the breaking strength is 80MPa to 100MPa, for example, 80MPa, 82.5MPa, 85MPa, 88MPa, 90MPa, 93MPa, 96MPa, 98MPa or 100MPa, etc.; the first power of the particle size D50 of the single crystal cobalt-free positive electrode material is recorded as e, the breaking strength of the single crystal cobalt-free positive electrode material is recorded as f, and e×f is 100 to 200MPa*μm.
[0054] Preferably, the single crystal cobalt-free positive electrode material has an indentation hardness of 8 GPa to 15 GPa, for example, 8 GPa, 9 GPa, 10 GPa, 11 GPa, 12 GPa, 13 GPa, 14 GPa or 15 GPa, etc.; the Young's modulus is 150 GPa to 180 GPa, for example, 150 GPa, 155 GPa, 160 GPa, 165 GPa, 170 GPa, 175 GPa or 180 GPa, etc.; the ratio of Young's modulus to indentation hardness is 10 to 23, for example, 10, 12, 14, 15, 17, 18, 20, 21, 22 or 23, etc.
[0055] Preferably, in the XRD spectrum of the single crystal cobalt-free positive electrode material, the ratio of the (003) characteristic diffraction peak intensity to the (101) characteristic diffraction peak intensity is 2.0 to 2.5, such as 2.0, 2.1, 2.2, 2.3 or 2.5, etc.; the ratio of the (003) characteristic diffraction peak intensity to the (104) characteristic diffraction peak intensity is 1.5 to 1.8, such as 1.5, 1.6, 1.7 or 1.8, etc. By designing the above-mentioned reasonable crystal structure orientation, it is helpful to improve the cycle stability and reduce the Li / Ni mixing.
[0056] In a third aspect, the present invention provides a lithium-ion battery, wherein the positive electrode of the lithium-ion battery comprises the single crystal cobalt-free positive electrode material described in the second aspect.
[0057] Compared with the prior art, the present invention has the following beneficial effects:
[0058] The method of the present invention utilizes acid etching of polycrystalline cobalt-free positive electrode materials, and performs lithium addition and sintering to obtain single-crystal cobalt-free positive electrode materials, which can obtain positive electrode materials with primary particle dispersion, improve rate performance and cycle performance, and can be used as a recycling strategy for polycrystalline positive electrode materials.
[0059] Furthermore, compared with sulfuric acid, hydrochloric acid and nitric acid, organic acid containing three elements of C, H and O is used for etching. Impurity elements such as S, Cl and N will not be introduced due to decomposition, and there will be no effect on the later positive electrode electrical performance.
[0060] By designing the indentation hardness, Young's modulus, and fracture strength of the cobalt-free cathode material after acid treatment, that is, rationally designing the above parameters of the primary cobalt-free particles, the mechanical properties of the cobalt-free single crystal cathode material can be effectively improved, which is helpful for developing batteries with high compaction and high volume energy density. By designing the above rational crystal structure orientation, it is helpful to improve the cycle stability and reduce the Li / Ni mixing. DETAILED DESCRIPTION
[0061] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0062] Example 1
[0063] This embodiment provides a method for preparing a single crystal cobalt-free positive electrode material, comprising the following steps:
[0064] Step 1: Prepare cobalt-free cathode material by mixing 48.94g of lithium salt Li2CO3 and 100g of cobalt-free precursor Ni 0.65 Mn 0.35 After (OH)2 and 0.3g TiO2 were uniformly mixed with a handheld blender, the particle size D50 of the cobalt-free precursor was 3.0μm, the fracture strength F was 12.2MPa, the product of the fracture strength and the second power of the particle size D50 of the cobalt-free precursor was 21.13MPa*μm, the indentation hardness (H) of the cobalt-free precursor was 2.46GPa, the Young's modulus (E) was 43.5GPa, and the ratio of Young's modulus to indentation hardness (W) was 17.7. The temperature was raised to 800℃ at 2℃ / min for high temperature reaction for 10h, and then cooled to room temperature at 4℃ / min for ultracentrifugal grinding and sieving;
[0065] Step 2: Add 5g of the prepared cobalt-free positive electrode material to 100mL of the prepared 1mol / L oxalic acid solution, stir at 30°C for 12h, collect the powder after filtration, wash it with deionized water for more than three times, then wash it with ethanol three times, put it into an oven, and dry it at 80°C for 12h. The dried positive electrode material is sieved to obtain a cobalt-free positive electrode powder. The particle size D50 of the prepared cobalt-free positive electrode material is 1.1μm, and the fracture strength F is 31.2MPa. The product of the fracture strength and the half of the particle size D50 of the cobalt-free positive electrode material is 32.72MPa*μm, the indentation hardness (H) is 6.5GPa, the Young's modulus (E) is 91.6GPa, the ratio of Young's modulus to indentation hardness (W) is 14.1, the ratio of the (003) characteristic diffraction peak intensity to the (101) characteristic diffraction peak intensity in XRD is 2.1, and the ratio of the (003) characteristic diffraction peak intensity to the (104) characteristic diffraction peak intensity is 1.7;
[0066] In the third step, 100 g of the cobalt-free positive electrode material powder obtained in the second step was uniformly mixed with 5 g of Li2CO3 and 0.3 g of Al2O3, and then sieved and sintered at 980°C for 10 h to obtain the cobalt-free positive electrode material. The cobalt-free positive electrode Al2O3 coverage was 78.3%, the cobalt-free positive electrode material particle size D50 was 2.8 μm, and the fracture strength F was 91.6 MPa, which was comparable to the cobalt-free positive electrode material. The product of the first half of the particle size D50 is 153.3MPa*μm, the indentation hardness (H) is 12.5GPa, the Young's modulus (E) is 168GPa, the ratio of Young's modulus to indentation hardness (W) is 13.44, the ratio of the (003) characteristic diffraction peak intensity to the (101) characteristic diffraction peak intensity in XRD is 2.0, and the ratio of the (003) characteristic diffraction peak intensity to the (104) characteristic diffraction peak intensity is 1.5;
[0067] Example 2
[0068] Example 2 is different from Example 1 in that the cobalt-free precursor used is Ni 0.75 Mn 0.25 (OH)2.
[0069] Example 3
[0070] Example 3 is different from Example 1 in that the lithium salt used in the first step is 48.9 g of LiOH.
[0071] Example 4
[0072] The difference between Example 4 and Example 1 is that the first step sintering temperature is 850°C.
[0073] Example 5
[0074] The difference between Example 5 and Example 1 is that the organic acid solution used in the second step is benzoic acid.
[0075] Example 6
[0076] The difference between Example 6 and Example 1 is that the sintering temperature used in the third step is 990°C.
[0077] Comparative Example 1
[0078] Comparative Example 1 is different from Example 1 in that the fracture strength F of the precursor used in the first step is 5.2 MPa, the product of the fracture strength and the square root of the particle size is 9 MPa*μm, the indentation hardness (H) of the precursor is 1.5 GPa, the Young's modulus (E) is 28.6 GPa, and the ratio of Young's modulus to indentation hardness (W) is 19. The product is reacted at a high temperature of 800°C for 10 hours, cooled, and then ultracentrifugal ground and sieved.
[0079] The fracture strength of the precursor in this comparative example is lower than the reasonable range, and the synthesis process leads to structural collapse.
[0080] Comparative Example 2
[0081] Comparative Example 2 is different from Example 1 in that the fracture strength F of the precursor used in the first step is 21.5 MPa, the product of the fracture strength and the half of the particle size D50 of the cobalt-free precursor is 37.2 MPa*μm, the indentation hardness (H) is 5.2 GPa, the Young's modulus (E) is 60.8 GPa, and the ratio of Young's modulus to indentation hardness (W) is 11.7. The product is reacted at a high temperature of 800°C for 10 hours, cooled, and then ultracentrifugal ground and sieved.
[0082] The fracture strength of this comparative example is higher than the reasonable range, the synthesis process is not conducive to the diffusion of Li ions, and the synthesis rate of the positive electrode material is poor.
[0083] Comparative Example 3
[0084] Comparative Example 3 is different from Example 1 in that the breaking strength F of the cobalt-free positive electrode material obtained in the second step is 15.3 MPa, the product of the breaking strength and the half of the particle size D50 of the cobalt-free positive electrode material is 16.0, the product of the breaking strength and the half of the particle size is 14.0 MPa*μm, the indentation hardness (H) is 3.8 GPa, the Young's modulus (E) is 58.5 GPa, and the ratio of Young's modulus to indentation hardness (W) is 15.4.
[0085] The positive electrode material synthesized in this comparative example is too fine and remains polycrystalline during the sintering process.
[0086] Comparative Example 4
[0087] The difference from Example 1 is that in the XRD of the cobalt-free positive electrode material prepared in the second step, the ratio of the (003) characteristic diffraction peak intensity to the (101) characteristic diffraction peak intensity is 1.5, and the ratio of the (003) characteristic diffraction peak intensity to the (104) characteristic diffraction peak intensity is 1.0.
[0088] The positive electrode material synthesized in this comparative example has a too short c-axis in its crystal structure, which is not conducive to lithium replenishment in the later stage.
[0089] Comparative Example 5
[0090] Comparative Example 5 is different from Example 1 in that the cobalt-free positive electrode material obtained in the third step has a fracture strength F of 75 MPa, a product of the fracture strength and the square root of the particle size is 125.4 MPa*μm, an indentation hardness (H) of 7.8 GPa, a Young's modulus (E) of 90 GPa, and a ratio of Young's modulus to indentation hardness (W) of 11.5.
[0091] The cobalt-free positive electrode material synthesized in this comparative example has low fracture strength and agglomerates with weak binding force.
[0092] Comparative Example 6
[0093] Comparative Example 6 is different from Example 1 in that the cobalt-free positive electrode material obtained in the third step has a fracture strength F of 120 MPa, the product of the fracture strength and the half of the particle size D50 of the cobalt-free positive electrode material is 200.8 MPa*μm, the indentation hardness (H) is 18.2 GPa, the Young's modulus (E) is 286.6 GPa, and the ratio of Young's modulus to indentation hardness (W) is 15.74.
[0094] The grains of the cobalt-free positive electrode material synthesized in this comparative example are too coarse, and there are phenomena such as metal segregation and oxygen loss.
[0095] Comparative Example 7
[0096] Comparative Example 7 is different from Example 1 in that the ratio of the (003) characteristic diffraction peak intensity to the (101) characteristic diffraction peak intensity in the XRD of the cobalt-free positive electrode material prepared in the third step is 3.0, and the ratio of the (003) characteristic diffraction peak intensity to the (104) characteristic diffraction peak intensity is 3.
[0097] The positive electrode material synthesized in this comparative example has a larger c-axis in its crystal structure.
[0098] Comparative Example 8
[0099] Comparative Example 8 is different from Example 1 in that the ratio of the (003) characteristic diffraction peak intensity to the (101) characteristic diffraction peak intensity in the XRD of the cobalt-free positive electrode material prepared in the third step is 2.5, and the ratio of the (003) characteristic diffraction peak intensity to the (104) characteristic diffraction peak intensity is 1.0.
[0100] The a-axis of the crystal structure of the positive electrode material synthesized in this comparative example is relatively small.
[0101] Comparative Example 9
[0102] Comparative Example 9 is different from Example 1 in that the material used is a commercially available normally prepared cobalt-free positive electrode material.
[0103] Comparative Example 10
[0104] Comparative Example 10 is different from Example 1 in that the acid solution used in the second step is a 1 mol / L sulfuric acid solution.
[0105] Button assembly: The metal lithium sheet is used as the negative electrode, and the positive electrode material prepared in Examples 1 to 6 and Comparative Examples 1 to 10 is used to prepare the positive electrode sheet. The prepared positive electrode sheet uses NMP as a solvent, and the mass ratio of the positive electrode material, the binder (PVDF), and the conductive agent (SP) is 96:2:2. After being mixed evenly, it is coated on the aluminum foil. The solid content of the PVDF glue is 6.05%, the thickness of the aluminum foil is 12μm, the purity is more than 99%, and the sheet is compacted to 3.3g / cm 3 , assembled into a button half-cell in a vacuum glove box with Celgand2325 separator.
[0106] Table 1 shows the electrical properties of Examples 1 to 6 and Comparative Examples 1 to 10 (charge cut-off voltage is 4.5 V, discharge cut-off voltage is 3.0 V, and nominal gram capacity is 200 mAh / g).
[0107] Table 1
[0108]
[0109] It can be seen from the above that the method of the present invention can obtain a high-performance single-crystal positive electrode material, which exhibits excellent rate performance and cycle performance.
[0110] By comparing Examples 1 to 6 with Comparative Example 9, it can be seen that the cobalt-free positive electrode material synthesized by the present invention has a 4C rate performance improved by 2% and a cycle retention rate improved by 2% compared to the commercially available cobalt-free positive electrode material. The crystal structure grown by the fine grain growth method adopted by the present invention is stable and the lithium ion dynamics are excellent.
[0111] By comparing Examples 1 to 6 with Comparative Example 1, it can be seen that when the fracture strength of the precursor used is lower than the target value, the precursor structure collapses during the synthesis process, resulting in the synthesized positive electrode material Li / Ni, which is not conducive to the kinetic process of lithium ion transmission, thereby deteriorating the rate performance. By comparing with Comparative Example 2, it can be seen that when the fracture strength of the precursor used is greater than the target value, the synthesis process is not conducive to Li + The uniform diffusion of the synthesized positive electrode material leads to poor conductivity, thus affecting the Li + The kinetic transmission process deteriorates the rate performance.
[0112] It can be seen from the comparison between Examples 1 to 6 and Comparative Example 3 that the fracture strength of the grown grains synthesized in the second step is lower than the target value, the particles are too small and fragile, and it is difficult to sinter them into single crystal materials in the subsequent sintering process, so the cycle performance deteriorates. Since the primary particle size of the polycrystalline positive electrode material is too small, large particles with too high fracture strength will not be produced, so the present invention is not analyzed;
[0113] By comparing Examples 1 to 6 with Comparative Example 4, it can be seen that the cobalt-free positive electrode grains synthesized in the second step, the ratio of the (003) characteristic diffraction peak intensity to the (101) characteristic diffraction peak intensity and the ratio of the (003) characteristic diffraction peak intensity to the (104) characteristic diffraction peak intensity are lower than the target value, and the synthesized positive electrode material has a shorter c-axis, which affects the subsequent lithium replenishment process, resulting in the final synthesized positive electrode material having fewer mobile lithium ions, slow kinetics, and poor rate performance.
[0114] By comparing Examples 1 to 6 with Comparative Example 5, it can be seen that the final synthesized cobalt-free positive electrode material has too low fracture strength. This is because there are a large number of weakly bound aggregates in the synthesized positive electrode material, which leads to the destruction of the structure after subsequent rolling into pole pieces, resulting in poor cycle performance and rate performance. By comparing with Comparative Example 6, it can be seen that the fracture strength of the synthesized cobalt-free positive electrode material becomes larger and the rate performance is poor. This is because the grain size of the synthesized cobalt-free positive electrode material is relatively coarse, which leads to a metal segregation process and poor performance.
[0115] By comparing Examples 1 to 6 with Comparative Example 7, it can be seen that when the cobalt-free positive electrode synthesized in the third step, the ratio of the (003) characteristic diffraction peak intensity to the (101) characteristic diffraction peak intensity in XRD is higher than the target value, the c-axis of the synthesized positive electrode material is larger, which leads to structural collapse during the subsequent battery cycle, especially under high-rate charge and discharge, the structural collapse is more serious, so the rate performance deteriorates. By comparing with Comparative Example 8, it can be seen that the ratio of the (003) characteristic diffraction peak intensity to the (104) characteristic diffraction peak intensity is lower than the target value, which leads to the a-axis being too low in the crystal structure of the synthesized positive electrode material, and there is an irreversible phase change process during the battery cycle, which leads to poor electrochemical performance.
[0116] Comparison of Examples 1 to 7 with Comparative Example 10 shows that the use of sulfuric acid to prepare the material leads to poor cycle performance. This is because the use of sulfuric acid will lead to the introduction of S impurities due to the S shuttle effect, resulting in poor cycle performance.
[0117] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a single crystal cobalt-free positive electrode material, characterized in that: The method comprises the following steps: Adding the polycrystalline cobalt-free positive electrode material to an acid solution, stirring for 8 h to 20 h at 30° C. to 60° C. for acid treatment, wherein the concentration of the acid solution is 1 mol / L to 2 mol / L; The acid-treated cobalt-free positive electrode material is mixed with the first lithium salt and sintered to obtain a single crystal cobalt-free positive electrode material; The sintering temperature is 900°C to 1100°C; The particle size D50 of the cobalt-free positive electrode material after acid treatment is 0.8 μm to 1.5 μm, and the fracture strength is 30 MPa to 45 MPa. The first power of the particle size D50 of the cobalt-free positive electrode material after acid treatment is recorded as a, and the fracture strength of the cobalt-free positive electrode material after acid treatment is recorded as b, and a×b is 25 MPa*μm to 60 MPa*μm; In the XRD spectrum of the cobalt-free positive electrode material after the acid treatment, the ratio of the (003) characteristic diffraction peak intensity to the (101) characteristic diffraction peak intensity is 2.0 to 2.5, and the ratio of the (003) characteristic diffraction peak intensity to the (104) characteristic diffraction peak intensity is 1.5 to 1.8; The preparation method of the polycrystalline cobalt-free positive electrode material comprises the following steps: mixing a second lithium salt, a cobalt-free precursor and a dopant, and reacting them at a high temperature, wherein the temperature of the high temperature reaction is 700° C. to 900° C.; In the preparation method of the polycrystalline cobalt-free positive electrode material, the particle size D50 of the cobalt-free precursor is 2.5-3.5 μm, the fracture strength is 10-15 MPa, the first power of the particle size D50 of the cobalt-free precursor is recorded as c, the fracture strength of the cobalt-free precursor is recorded as d, and c×d is 14-30 MPa*μm; The particle size D50 of the single crystal cobalt-free positive electrode material is 2.5μm to 3.5μm, the fracture strength is 80MPa to 100MPa, the product of the fracture strength and the square root of the particle size D50 of the single crystal cobalt-free positive electrode material is 100 to 200MPa*μm, the indentation hardness is 8GPa to 15GPa, the Young's modulus is 150GPa to 180GPa, the ratio of Young's modulus to indentation hardness is 10 to 23, the ratio of the (003) characteristic diffraction peak intensity to the (101) characteristic diffraction peak intensity in XRD is 2.0 to 2.5, and the ratio of the (003) characteristic diffraction peak intensity to the (104) characteristic diffraction peak intensity is 1.5 to 1.
8.
2. The preparation method according to claim 1, characterized in that: The acid in the acid solution includes at least one of an organic acid, sulfuric acid, hydrochloric acid and nitric acid.
3. The preparation method according to claim 2, characterized in that: The acid in the acid solution is an organic acid.
4. The preparation method according to claim 3, characterized in that: The organic acid includes at least one of formic acid, acetic acid, propionic acid, butyric acid, caprylic acid, adipic acid, oxalic acid, malonic acid, succinic acid, maleic acid, tartaric acid, benzoic acid, phenylacetic acid, phthalic acid, terephthalic acid, valeric acid, caproic acid, capric acid, stearic acid and palmitic acid.
5. The preparation method according to claim 1, characterized in that: During the acid treatment, the amount of polycrystalline cobalt-free positive electrode material added is 0.02 g / mL to 0.1 g / mL.
6. The preparation method according to claim 1, characterized in that: The acid treatment is followed by separation, washing and drying steps.
7. The preparation method according to claim 1, characterized in that: The indentation hardness of the cobalt-free positive electrode material after acid treatment is 4 GPa to 15 GPa, the Young's modulus is 60 GPa to 150 GPa, and the ratio of the Young's modulus to the indentation hardness is 10 to 15.
8. The preparation method according to claim 1, characterized in that: The added amount of the first lithium salt accounts for 5% to 10% of the mass of the cobalt-free positive electrode material after the acid treatment.
9. The preparation method according to claim 1, characterized in that: The sintering time is 8h to 20h.
10. The preparation method according to claim 1, characterized in that: The raw materials used for mixing the acid-treated cobalt-free positive electrode material also include a coating agent, and the coating agent includes at least one of ZrO2, Al2O3, Ta2O5, MoO3, SiO2, Y2O5, MgO, TiO2, WO3, Nb2O5, SrCO3 and La2O5.
11. The preparation method according to claim 10, characterized in that: Based on the mass of the single crystal cobalt-free positive electrode material, the usage amount of the coating agent is 1000ppm to 3000ppm.
12. The preparation method according to claim 1, characterized in that: The polycrystalline cobalt-free positive electrode material is recovered from waste lithium batteries or prepared from raw materials.
13. The preparation method according to claim 1, characterized in that: In the method for preparing the polycrystalline cobalt-free positive electrode material, the cobalt-free precursor is Ni 0.65+a Mn 0.35-a (OH)2, where 0.00≤a≤0.
25.
14. The preparation method according to claim 1, characterized in that: In the method for preparing the polycrystalline cobalt-free positive electrode material, the cobalt-free precursor has an indentation hardness of 2 GPa to 3 GPa, a Young's modulus of 30 GPa to 60 GPa, and a ratio of Young's modulus to indentation hardness of 15 to 30.
15. The preparation method according to claim 1, characterized in that: In the preparation method of the polycrystalline cobalt-free positive electrode material, the dopant includes at least one of ZrO2, Al2O3, Ta2O5, MoO3, SiO2, Y2O5, MgO, TiO2, WO3, Nb2O5 and SrCO3.
16. The preparation method according to claim 1, characterized in that: Based on the single crystal cobalt-free positive electrode material, the dosage of the dopant is 500 to 5000 ppm.
17. The preparation method according to claim 1, characterized in that: In the method for preparing the polycrystalline cobalt-free positive electrode material, the high-temperature reaction time is 8 hours to 12 hours.
18. The preparation method according to claim 1, characterized in that: In the preparation method of the polycrystalline cobalt-free positive electrode material, the heating rate of the high-temperature reaction is 2°C / min to 6°C / min, the cooling rate is 4°C / min to 6°C / min, and the ratio of the cooling rate to the heating rate is 2 to 3.
19. The preparation method according to claim 1, characterized in that: The method The following steps are involved: Step 1: Prepare a cobalt-free positive electrode material. After the second lithium salt, the cobalt-free precursor and the dopant are uniformly mixed with a handheld blender, the particle size D50 of the cobalt-free precursor is 2.5-3.5 μm, the fracture strength is 10-15 MPa, the product of the fracture strength and the second power of the particle size D50 of the cobalt-free precursor is 14-30 MPa*μm, the indentation hardness of the cobalt-free precursor is 2 GPa-3 GPa, the Young's modulus is 30 GPa-60 GPa, and the ratio of the Young's modulus to the indentation hardness is 15-30. The reaction is carried out at a high temperature of 700°C-900°C for 8h-12h, and then ultracentrifugal grinding and sieving are performed after cooling; Step 2: Add the prepared cobalt-free cathode material to 1 mol / L to 2 mol / L oxalic acid solution, stir at 30°C to 60°C for 8h to 20h, collect the powder after filtration, wash it with deionized water for more than three times, then wash it with ethanol for three times, put it into an oven to dry, sieve the dried cathode material to obtain cobalt-free cathode powder, and the particle size D50 of the prepared cobalt-free cathode material is 0.8μm to 1.5μm, and the fracture strength is 30MPa to 45MPa, which is similar to that of the cobalt-free cathode material. The product of the first power of the particle size D50 of the cobalt positive electrode material is 25MPa*μm to 60MPa*μm, the indentation hardness is 4GPa to 15GPa, the Young's modulus is 60GPa to 150GPa, the ratio of the Young's modulus to the indentation hardness is 10 to 15, the ratio of the (003) characteristic diffraction peak intensity to the (101) characteristic diffraction peak intensity in XRD is 2.0 to 2.5, and the ratio of the (003) characteristic diffraction peak intensity to the (104) characteristic diffraction peak intensity is 1.5 to 1.8; The third step is to take the cobalt-free positive electrode material powder obtained in the second step, mix it evenly with the first lithium salt and the coating agent, and then sieve it to obtain the single crystal cobalt-free positive electrode material after keeping it at 900°C to 1100°C for 8h to 20h, and obtain the single crystal cobalt-free positive electrode material. The particle size D50 of the single crystal cobalt-free positive electrode material is 2.5μm to 3.5μm, the fracture strength is 80MPa to 100MPa, and the fracture strength is proportional to the square of the half of the particle size D50 of the single crystal cobalt-free positive electrode material. The product is 100~200MPa*μm, the indentation hardness is 8GPa~15GPa, the Young's modulus is 150GPa~180GPa, the ratio of Young's modulus to indentation hardness is 10~23, the ratio of the (003) characteristic diffraction peak intensity to the (101) characteristic diffraction peak intensity in XRD is 2.0~2.5, and the ratio of the (003) characteristic diffraction peak intensity to the (104) characteristic diffraction peak intensity is 1.5~1.
8.
20. A single crystal cobalt-free positive electrode material prepared by the method according to any one of claims 1 to 19; The particle size D50 of the single crystal cobalt-free positive electrode material is 2.5 μm to 3.5 μm, and the fracture strength is 80 MPa to 100 MPa. The first power of the particle size D50 of the single crystal cobalt-free positive electrode material is recorded as e, and the fracture strength of the single crystal cobalt-free positive electrode material is recorded as f. e×f is 100 to 200 MPa*μm. The single crystal cobalt-free positive electrode material has an indentation hardness of 8 GPa to 15 GPa, a Young's modulus of 150 GPa to 180 GPa, and a ratio of Young's modulus to indentation hardness of 10 to 23; In the XRD spectrum of the single crystal cobalt-free positive electrode material, the ratio of the (003) characteristic diffraction peak intensity to the (101) characteristic diffraction peak intensity is 2.0-2.5, and the ratio of the (003) characteristic diffraction peak intensity to the (104) characteristic diffraction peak intensity is 1.5-1.
8.
21. The single crystal cobalt-free positive electrode material according to claim 20, characterized in that: The metal oxide coverage on the surface of the single crystal cobalt-free positive electrode material is 60% to 80%.
22. A lithium ion battery, characterized in that: The positive electrode of the lithium-ion battery includes the single crystal cobalt-free positive electrode material according to claim 20 or 21.
Citation Information
Patent Citations
Method for reconstructing ternary single crystal material from waste ternary polycrystalline material
CN112391671A
Positive electrode material of lithium ion battery and preparation method thereof
CN111430678A
Monocrystal ternary positive electrode material and preparation method and application thereof
CN113753971A
Method for refining cobalt-free positive electrode material, cobalt-free positive electrode material and lithium ion battery
CN114988497A